2016
DOI: 10.3389/fphar.2016.00430
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells Inhibit Bleomycin-Induced Pulmonary Fibrosis in Mice through Suppressing TGF-β1/Smad-Mediated Epithelial to Mesenchymal Transition

Abstract: Pulmonary fibrosis is a progressive and irreversible fibrotic lung disorder with high mortality and few treatment options. Recently, induced pluripotent stem (iPS) cells have been considered as an ideal resource for stem cell-based therapy. Although, an earlier study demonstrated the therapeutic effect of iPS cells on pulmonary fibrosis, the exact mechanisms remain obscure. The present study investigated the effects of iPS cells on inflammatory responses, transforming growth factor (TGF)-β1 signaling pathway, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…It is well known that TGF-β1 is a key cytokine leading to EMT and TGF-β1overexpression is associated with poorer prognosis in ARDS [23,33] .The downstream effects of TGF-β1 are mediated by Smad2/3, while Smad7 can bind TGF-βR1and prevent TGF-β-associated Smad signaling [33] . It has been demonstrated that TGF-β1induced EMT in alveolar epithelial cells both in vivo and in vitro via Smad2/3 activation [34,35] . In parallel with these observations, we found that expression of TGF-β1, TGF-βR1, p-Smad2 were all upregulated in the brotic lung tissue while Smad7 was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that TGF-β1 is a key cytokine leading to EMT and TGF-β1overexpression is associated with poorer prognosis in ARDS [23,33] .The downstream effects of TGF-β1 are mediated by Smad2/3, while Smad7 can bind TGF-βR1and prevent TGF-β-associated Smad signaling [33] . It has been demonstrated that TGF-β1induced EMT in alveolar epithelial cells both in vivo and in vitro via Smad2/3 activation [34,35] . In parallel with these observations, we found that expression of TGF-β1, TGF-βR1, p-Smad2 were all upregulated in the brotic lung tissue while Smad7 was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary fibrosis (PF), characterized by exaggerated accumulation of extracellular matrix (ECM) proteins, is a progressive and irreversible fatal lung disease with a median survival time less than 3 years ( King et al, 2011 ; Warsinske et al, 2016 ; Li and Kan, 2017 ). Although the etiology of PF is still unclear, emerging studies have shown that some special type of cells and cytokines play vital roles in the process of PF ( Li et al, 2014b ; Zhou et al, 2016 ). Several treatment strategies including the anti-fibrinolytic composition, glucocorticoids, and anti-oxidants have been proved to be effective in the laboratory studies or human PF.…”
Section: Introductionmentioning
confidence: 99%
“…Because the HBEC PKM cell line shows mesenchymal-like behavior (6), the SMAD2/3 down-regulated subpopulation was not expected (26,27). Thus, we next chose to investigate if alterations in SMAD2/3 signaling are genuinely oncogene-related.…”
Section: Resultsmentioning
confidence: 99%